Assessing customer satisfaction towards service quality in the hospitality industry / Siti Rapidah Omar Ali ... [et al.] - Omar Ali, Siti Rapidah; Norizan, Siti Norsuhaizam; Mohd Said, Nur Shafini; Mat, Khalid Amin; Jislan, Fatanah (Universiti Teknologi MARA, Perlis, 2021)
It is proven true that the main subjects addressed by every service industry nowadays are service quality and customer satisfaction. Hence, virtuous customers' evaluation of services is crucial for the firms. Delivering good quality service is leading to attain today’s competitive environment. This study attempts to assess the relationship between service quality and customer satisfaction in the hotel industry in Malaysia. SERVQUAL model of service quality has been used to measure the relationship between three independent variables namely Tangibility, Reliability and Responsiveness and a dependent variable that is customer satisfaction. A number of 217 hotel guests in a three-star hotel in Kuala Terengganu were selected as a sample by using a convenience sampling method. A questionnaire was used as the research instrument in a survey approach. The findings indicated that all three dimensions of service quality have a positive relationship with customer satisfaction. Responsiveness seems to be the most significant factor in satisfaction. This study contributes to the enhancement and standardization of service quality management in firms especially the hotel industry in Malaysia. The findings would offer a better understanding and recommendations for hotel management transformation and practices.